Polymer-based drug-eluting stent treatment extends the time to reintervention for patients with symptomatic femoropopliteal artery disease: clinical evidence and potential economic value - Yoshimitsu Soga; Masahiko Fujihara; Osamu Iida; Anvar Babaev; Daizo Kawasaki; Thomas Zeller; David O'Connor; Anna M Chavez; Stefan Muller-Hulsbeck; Michael R Jaff (Becaris Publishing Limited, 2024)
Aim: Use long-term follow-up data from the IMPERIAL study to determine whether drug-eluting polymer based nitinol stent treatment can delay the time to repeat intervention for femoropopliteal artery disease and how such a delay may result in cost savings in a value-based episode of care. Patients & methods: The IMPERIAL randomized controlled trial was an international study of a paclitaxel-eluting polymer coated stent (Eluvia, Boston Scientific, MA, USA) versus a polymer-free paclitaxel-coated stent (Zilver PTX, Cook Corporation, IN, USA) for treating lesions of the femoropopliteal arterial segment. Study patients (n = 465) had symptomatic lower limb ischemia. Safety and efficacy assessments were performed through 5 years. Mean time to first reintervention was calculated in post-hoc analysis for patients who underwent a clinically driven target lesion revascularization (CD-TLR) through 3 or 5 years following the index procedure. To simulate potential cost savings associated with differential CD-TLR burden over time, a cost-avoidance analysis using input parameters from IMPERIAL and US 100% Medicare standard analytical files was developed. Results: Among patients with a first CD-TLR through 3 years of follow-up, mean time to reintervention was 5.5 months longer (difference 166 days, 95% CI: 51, 282 days; p = 0.0058) for patients treated with Eluvia (n = 56) than for those treated with Zilver PTX (n = 30). Through the 5-year study follow up period, CD-TLR rates were 29.3% (68/232) for Eluvia and 34.2% (39/114) for Zilver PTX (p = 0.3540) and mean time to first reintervention exceeded 2 years for patients treated with Eluvia at 737 days versus 645 days for the Zilver PTX group (difference 92 days, 95% CI: -85, 269 days; p = 0.3099). Simulated savings considering reinterventions occurring over 1 and 5 years following initial use of Eluvia over Zilver PTX were US $1,395,635 and US $1,531,795, respectively, when IMPERIAL CD-TLR rates were extrapolated to 1000 patients. Conclusion: IMPERIAL data suggest initial treatment with Eluvia extends the time patients spend without undergoing reintervention. This extension may be associated with cost savings in relevant time frames.